Keterpilihan Dinasti Politik pada Pilkada Kabupaten/Kota di Indonesia Tahun 2017-2020 - Yuliartiningsih, Theresia Wahyuni; Adrison, Vid (Jurnal Kebijakan Ekonomi, 2022)
The main purpose of this study was to examine whether the health variable as proxied by government health insurance participation and the infrastructure variable as a proxy for steady road conditions were correlated with the electability of political dynasties in the district/city elections in Indonesia in 2017-2020. This study tested using an average of 5 years before the 2017, 2018 and 2020 elections and the sample used was 508 districts/cities. This study uses a probit and a heck-probit regression model. The results of the selection bias control show that the health interest variable, namely BPJS Non-PBI, significantly reduces the probability of being elected to a political dynasty. This negative direction is a form of retrospective economic voting in political dynasties. Voters consider that the government has no role in providing free health facilities. Voters must pay BPJS Non-PBI membership dues through their employers or pay them independently. Meanwhile, the infrastructure interest variable in the form of steady road conditions significantly increases the probability of being elected to a political dynasty. This indicates that improving road conditions is effective in increasing the electability of political dynasties and the community makes road conditions a tool for retrospective economic voting in political dynasties.